The political economy of competitiveness in the new world economy: The case of Canada under the Progressive Conservatives, 1984-1993. - Paterson, Christopher A. (University of Ottawa (Canada), 1996)
This thesis examines recent transformations in international political economy, particularly the role of the nation-state in responding to the challenge of competitiveness within a new world economy characterized by globalization and technological innovation. Developing a typology of competitiveness from a survey of four leading new theories of economic competitiveness, the thesis presents a hypothesis that an evolving, post-fordist regime of accumulation shaping the new world economy requires new means of state intervention in trade, foreign investment, innovation promotion and other specific policy areas. Applying selected case studies of federal privatizations in Canada under the Progressive Conservative governments of Brian Mulroney from 1984 to 1993--a policy area central to the Mulroney Governments' neoconservative agenda--against the typology of competitiveness clearly indicates that when confronted with the conflicting imperatives of global markets and economic prosperity, governments will likely choose to intervene to protect and promote the latter than pay homage to the former. The results of the thesis' analyses challenge the viability of neoconservative ideology and particularly the effectiveness of free market policies to respond to the challenge of economic competitiveness in the new world economy, presenting a renewed case for progressive and proactive state intervention.
Keywords: History, Canadian.